1992
DOI: 10.1056/nejm199206043262303
|View full text |Cite
|
Sign up to set email alerts
|

Mortality among Infants of Black as Compared with White College-Educated Parents

Abstract: In contrast to black infants in the general population, black infants born to college-educated parents have higher mortality rates than similar white infants only because of their higher rates of low birth weight. Black and white infants of normal birth weight have equivalent mortality rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
92
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 322 publications
(108 citation statements)
references
References 12 publications
5
92
0
Order By: Relevance
“…In any case, the data from the seven cities strengthen the earlier conclusion: while lower status non-whites suffer from living in the lowest income area, the higher status non-whites benefit very little, in terms of their infant mortality levels, from living in the higher income areas. This is consistent with the findings of other studies which have suggested that it is the greater incidence of low birth weight among non-whites, even among higher status nonwhites, that accounts for the higher infant mortality rates at all class levels (Wise et al, 1985;Schoendorf et al, 1992). The fact that the overall incidence of deaths due to low birth weight in the seven-city aggregate was three times higher for non-whites than for whites supports this explanation (Stockwell & Goza, 1994).…”
Section: Age-cause Patterns 1990supporting
confidence: 91%
“…In any case, the data from the seven cities strengthen the earlier conclusion: while lower status non-whites suffer from living in the lowest income area, the higher status non-whites benefit very little, in terms of their infant mortality levels, from living in the higher income areas. This is consistent with the findings of other studies which have suggested that it is the greater incidence of low birth weight among non-whites, even among higher status nonwhites, that accounts for the higher infant mortality rates at all class levels (Wise et al, 1985;Schoendorf et al, 1992). The fact that the overall incidence of deaths due to low birth weight in the seven-city aggregate was three times higher for non-whites than for whites supports this explanation (Stockwell & Goza, 1994).…”
Section: Age-cause Patterns 1990supporting
confidence: 91%
“…Immigrants may pose a mixture of challenges for healthcare providers. In terms of women's health and particularly pregnancy outcome, various studies have described wide discrepancies in birth outcomes among different ethnic and racial populations that have immigrated to western countries [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Among infants and young children, for example, virtually all of the most prevalent mortalities and morbidities are associated with poverty and social neglect. Among these are perinatal drug use (Feldman et al, 1992); violence (Mason et al, 1992); lead poisoning (Fischer et al, 1993); and poor parental educational attainment (Schoendorf et al, 1992). Postnatal infectious diseases such as tuberculosis, HIV and AIDS (Snider et al, 1992), and infantile diarrhea (Ho et al, 1988) are likewise highly associated with poverty.…”
mentioning
confidence: 99%